Radosław Kotecki, The Prince and the Prandium: The Motif of the Pre-battle Lunch in the Monk of Sázava’s Account of the Battle of Chlumec (1126) - Kotecki, Radosław (Kwartalnik Historyczny, 2024)
This article delves into the Monk of Sázava’s narrative, a late twelfth-century continuation of Cosmas of Prague’s chronicle, which recounts the preparations of Prince Soběslav I of Bohemia for the battle of Chlumec against King Lothar III of Germany on 18 February 1126. In particular, the analysis centres on the motif of the lunch (prandium) that the Bohemian ruler is said to have shared with his men shortly before the battle. Through comparative examination and analysis, the article unveils a contrasting perspective. Unlike numerous narratives that castigate rulers for engaging in a meal prior to battle, the chronicler strategically employed this motif to elevate the character of the prince. This elevation was achieved by infusing the lunch with religious overtones.